The Practices Of Teaching And Learning English Pronunciation In Preparatory School. The Case Of Hasasa Preparatory School Grade 11 And 12 Students In West Arsi Zone, Oromia Region. - Mahammed Bayu (My University, 2015)
This study was mainly intended to explore the beliefs and practices prevailing in my working area specifically in Hasasa preparatory school about the practices of teaching and learning English pronunciation and to determine where on the continuum in the history of pronunciation teaching and learning, the attitudes that teachers and students have in connection with English pronunciation, focus given to it and the approach that needed to be employed. The practices of teaching and learning of English pronunciation in secondary and preparatory schools in Ethiopia has not received the attention it deserves. This is due to a number of factors ranging from experienced teachers to adoption of inappropriate approaches and techniques as well as unavailability of education media such as audio-visuals materials and even the number pronunciation lessons included in English textbooks of various grade levels is not the amount it deserves to be included in those textbooks. However, in the context of English as an international language, the teacher has to tackle the challenge of paying attention to those features that enable the learners to achieve acceptability and international intelligibility in order to communicate with the people whose English is their first language without any difficulty in pronunciation. To achieve this objective, the teacher needs to adopt certain techniques and approaches and the students themselves prepare themselves to learn and bring a revolutional change in it. Pertaining to the study itself, the challenges and techniques in teaching English pronunciation, the attitudes of students and teachers towards pronunciation, the relative focus given to it and the approaches of pronunciation teaching were examined. The questionnaire and interviews were developed and used to investigate the attitude dimension. The textbooks were assessed in the light of coverage, size, attention and procedures, which allowed the researcher to closely examine the focus and approach dimensions. Classroom observation was also used as a supplementary technique.